Curcumin as a permeability enhancer enhanced the antihyperlipidemic activity of dietary green tea extract - Ashlesha P. Pandit; Shreyas R. Joshi; Preeti S. Dalal; Vinita C. Patole (BMC, 2019)
Abstract Background Green tea has polyphenols like flavonoids and catechins; mainly epigallocatechin-3-gallate (EGCG), epicatechin gallate (ECG), epigallocatechin (EGC) and epicatechin (EC), out of which EGCG is of higher abundance. EGCG has shown preventive role in hypercholesterolemia. However, due to low oral bioavailability, a need arises to improve its membrane permeability and transporter-mediated intestinal efflux. Therefore, an attempt was made to enhance permeability and bioavailability of EGCG using curcumin to treat hyperlipidemia. Further, it was formulated in herbal tea bags to achieve patient compliance. Methods EGCG extracted from green tea leaves was confirmed by High Performance Thin Layer Chromatography. Green tea extract (GTE), curcumin and their mixtures were subjected to Fourier Transform Infra-Red spectroscopy and Differential Scanning Calorimetry for compatibility studies. Powder formulation was prepared comprising GTE, curcumin, sucralose and cardamom. Results Ex-vivo study was performed on everted goat intestine, analyzed by HPLC and demonstrated highest permeation of GTE:curcumin (220:50) (53.15%) than GTE (20.57%). Antihyperlipidemic activity was performed in rats for 15 days. Blood sample analysis of rats of test groups (formulation and GTE solution) fed on high fat diet showed (mg/dl):cholesterol 80 and 90, triglycerides 73.25 and 85.5, HDL 50.75 and 46, LDL 43.9 and 46, VLDL 14.65 and 17.1 respectively with significant lipid regulating effect. Conclusion Curcumin enhanced permeability of EGCG. Therefore, P-glycoprotein pump inside intestine can be potential mechanism to enhance permeability of EGCG. Thus, EGCG-curcumin herbal tea bag is promising nutraceutical to treat hyperlipidemia in day-to-day life achieving patient compliance.